Provision of quality learning guidelines to elementary school students in Pasir Sari Village South Cikarang - Elsye Fatmawati; Santi Kurnia (Central Community Development Journal, 2021)
This service activity aims to carry out quality tutoring at elementary schools in Pasir Sari village. The method used is a direct approach through the observation method by observing directly the teaching activities that occur during learning assistance. Data collection was also carried out by interviewing several elementary school students, especially students who took part in the learning mentoring program. As well as documentation studies by citing some data from the literature of journals and books. Thus, tutoring is very helpful for both children and parents. In addition, children's enthusiasm is proven by always asking when there will be another tutoring session. With the enthusiasm of students following the learning process in the morning and coupled with the selection of appropriate learning strategies or methods, it can improve student learning outcomes.